Analysis of the Effect of Regional Expenditure Management on the Level of Community Welfare in Papua Province - Jemy Ricardo Parera; Ayub Tanudy; Yuyunita; Ade Irma A. Srem; MaylenÂ K.P.Â Kambuaya; Hesty Theresia Salle; Quinci Fransiska Kambuaya; Siane Forince Siwa (PT Inovasi Pratama Internasional, 2023)
The objectives of this research are (1) to find out how much direct and indirect spending affect the poverty rate through economic growth, (2) to find out how much direct and indirect spending affect the HDI level through economic growth, (3) find out how much direct spending and indirect spending affect the gini ratio through economic growth. To fulfill the research objectives and test the hypotheses that have been set, the analysis used is path analysis to facilitate data processing, so the analysis used in processing the data is the Amos Program Version 22. The research results show that: a direct relationship between direct expenditure variables and growth The economic correlation shows a positive but not significant correlation. The direct expenditure variable has a negative and significant effect on poverty, both directly and through the economic growth variable. The results show that the direct spending of the Papua provincial government has an indirect effect on the poverty rate in this area. The direct expenditure variable has a positive effect on improving HDI performance, both directly and through economic growth variables. That is, the correlation between direct spending on regional inequality shows a positive relationship, both directly and through economic growth variables. Indirect spending variables have a negative relationship to economic growth in Papua province. The correlation between indirect spending on poverty levels in Papua province shows negative relationship, both directly and through economic growth. Indirect expenditure variables have a negative correlation with HDI performance, both directly and through economic growth variables. Furthermore, indirect expenditure variables have a positive correlation with regional inequality in this area, both indirectly directly or through intervening variables of economic growth.